2009
DOI: 10.1007/s12217-009-9133-9
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Non-axisymmetric Electrolyte Jet in High-frequency AC Electric Field

Abstract: In the present work linear instability of capillary non-axisymmetric micro-jets of electrolyte solutions in a high-frequency alternating axial electric field is investigated theoretically. The gravity affects are neglected. The problem is described by strongly coupled nonlinear system of PDEs for ion transport, electrical field and fluid flow. Viscous liquid is taken. The problem can be divided into outer and inner ones. Solution for the unsteady double ion layer is obtained in Debye-Huckel approximation provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It is easy to show that in this case there is no depence on Reynolds number in complete analogy with the classical Rayleigh case of electric field absence, The results were also compared with the ones obtained from the averaging theory (Polyanskikh and Demekhin 2009). It was shown that the latter gives very good approximation even at dimensionless frequency ω greater than 1 ÷ 2 for arbitrary values of other parameters (see Fig.…”
Section: Linear Stability Analysismentioning
confidence: 75%
See 4 more Smart Citations
“…It is easy to show that in this case there is no depence on Reynolds number in complete analogy with the classical Rayleigh case of electric field absence, The results were also compared with the ones obtained from the averaging theory (Polyanskikh and Demekhin 2009). It was shown that the latter gives very good approximation even at dimensionless frequency ω greater than 1 ÷ 2 for arbitrary values of other parameters (see Fig.…”
Section: Linear Stability Analysismentioning
confidence: 75%
“…In Polyanskikh and Demekhin (2009) it was shown that non-axisymmetric perturbations are always stable in the case of uncharged electrolyte jet in longitudinal electric field. This justifies consideration of the most important axisymmetric case.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations